109k views
5 votes
What is the following sum? Assume x > 0 and y > 0 sqrt x^2y^2+2 sqrt x^3y^4+xy sqrt y

2 Answers

6 votes

Answer:

B is the right option

Explanation:

On edg :))

User Vindia
by
5.3k points
3 votes

Answer:


xy(1+2y√(x)+√(y))

Explanation:

Given expression,


√(x^2y^2)+2√(x^3y^4)+xy√(y)


=(x^2y^2)^(1)/(2) + 2(x^3y^4)^(1)/(2) + xy√(y)


\because (√(x)=x^(1)/(2))


=(x^2)^(1)/(2) (y^2)^(1)/(2) + 2(x^3)^(1)/(2) (y^4)^(1)/(2) + xy√(y)


(\because (ab)^n=a^n b^n)


=x^{2* (1)/(2)} y^{2* (1)/(2)} + 2(x^{3* (1)/(2)})(y^{4* (1)/(2)})+xy√(y)


\because (a^n)^m=a^(mn)


=x^1 y^1 + 2x^{1(1)/(2)} y^2 + xy√(y)


=xy+2x.(x)^(1)/(2) y^2 + xy√(y)


=xy+2xy^2√(x)+xy√(y)


=xy(1+2y√(x)+√(y))

User Noahlz
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.